2019
DOI: 10.3146/ps17-20.1
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Fertilization as a Strategy to Increase the Proportion of Mature Pods in Peanut (Arachis hypogaea L.)

Abstract: Foliar application of nutrients is used by growers to remediate crop nutrient deficiencies, but anecdotal reports indicate there may be associated effects of accelerated crop maturity, particularly for irrigated peanut ( Arachis hypogaea L.). Research was conducted to determine whether application of foliar fertilizers during early pod set could increase the proportion of early-maturing pods, and thereby increase the mature proportion of the profile under irrigated conditions. Field experiments were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
1
1
0
2
Order By: Relevance
“…The results are in close conformity with the observations recorded by Sarkar et al, (1999) and Sarkar and Pal (2006), who also reported response of groundnut to the applied foliar nutrition. The same finding resemble with Veerabhadrappa and Yeledhalli (2005) and Veeramani et al, (2012); Chandrasekaran et al, (2008); Pierre et al, (2019).…”
Section: Resultssupporting
confidence: 87%
“…The results are in close conformity with the observations recorded by Sarkar et al, (1999) and Sarkar and Pal (2006), who also reported response of groundnut to the applied foliar nutrition. The same finding resemble with Veerabhadrappa and Yeledhalli (2005) and Veeramani et al, (2012); Chandrasekaran et al, (2008); Pierre et al, (2019).…”
Section: Resultssupporting
confidence: 87%
“…Discordando do presente estudo, Pierre et al (2019) testando adubações foliares com N (10 kg ha -1 ), P (1,0 kg ha -1 ) e B (0,34 kg ha -1 ) verificou que a aplicação foliar de B isolada não teve efeito sobre a porcentagem de plântulas normais. Provavelmente, isso se deve ao fato de o B ter uma mobilidade reduzida na planta amendoim (BROWN; SHELP, e2073 SAS, 1(2):e2073, 2020 1997), não ocorrendo redistribuição via floema do B absorvido através das folhas para as raízes e estruturas reprodutivas (MALAVOLTA et al, 1997).…”
Section: El Objetivo De Este Estudio Fue Evaluar La Calidad De Semillunclassified
“…(DECHEN et al, 1991;RÖMHELD, 2001;SINGH et al, 2007). Estudos mostrando o efeito positivo do B na maturação e de plântulas normais também foram demostrados por Pierre et al (2019); Singh et al (2007); Grichar et al, (2012); Nogueira e Santos (2000).…”
Section: El Objetivo De Este Estudio Fue Evaluar La Calidad De Semillunclassified
“…
The commercial blend of nitrogen, phosphorus, potassium, and fulvic acid, marketed as Peg Power (ammoniacal nitrogen at 1.31% (w/w), nitrate nitrogen at 0.32% (w/w), urea nitrogen at 5.37% (w/w), available phosphate at 4.0% (w/w), soluble potash at 9.0% (w/w), and fulvic acid complex at 12.0%; referred to as a blend of foliar fertilizer and fulvic acid) is promoted in some areas for use in peanut (Arachis hypogaea L) to maximize flowering, pod set, pod fill, and increase yield (Triangle Chemical, 2022). Data in the peer-reviewed literature is limited in terms of peanut yield response to foliarapplied fertilizers that include these elements (Pierre et al, 2019), and no information is published that compares peanut yield response to the blend of foliar fertilizer and fulvic acid to nontreated peanut. Research was conducted in North Carolina to determine if this product increases yield compared with nontreated peanut when applied sequentially at the R1 stage of peanut development (Boote, 1982) followed by a second application at the R3 stage of peanut development 2 wk later.
…”
mentioning
confidence: 99%